Interventions that enhance health-professional contact with parents and infants to improve child development and social and emotional wellbeing in the early years in high-income countries: a systematic review. (November 2016) - Hurt, Lisa; Paranjothy, Shantini; Lucas, Patricia J; Watson, Debbie; Mann, Mala; Griffiths, Lucy; Ginja, Samuel; Paljarvi, Tapio; Williams, Jo; Bellis, Mark; Lingam, Raghu
Abstract: Background: Experiences in the first 1000 days of life have a crucial influence on child development and health. Universal health services provide support for families during this time, but new unassessed components are often added. We systematically reviewed the evidence for interventions in high-income countries designed to improve child development by enhancing health professional contact with parents in the very early years. Methods: We searched Cochrane Central Register of Controlled Trials, Medline, Embase, CINAHL, PsycINFO, Web of Science, Scopus, ASSIA, LiLACS, Sociological Abstracts, Social Services Abstract, OpenGrey, ClinicalTrials.gov, UK Clinical Trials Gateway, and the WHO International Clinical Trials Registry Platform for studies published in any language between Jan 1, 1996, and Dec 17, 2014, using subject headings and key words with the following search structure: [health OR parenting professionals OR known programme names] AND [child development OR emotional/behavioural OR language OR cognitive outcomes]. We hand searched eight journals and 47 programme or organisation websites. We included randomised controlled trials (RCTs) that examined professional interventions designed to augment existing universal health-care provision from the antenatal period to 2 years post partum. Primary outcomes were motor, cognitive, and language development, and social and emotional wellbeing, measured to 3 years of age. Results were reported by narrative synthesis, because of heterogeneity in intervention design and outcome measurement. Findings: Of 12 473 studies identified, 21 RCTs met eligibility criteria. 15 had a high or unclear risk of bias as judged by Cochrane criteria. There was limited evidence for intervention effectiveness: some positive effects were seen in one of five studies for motor development, four of ten for language development, four of seven for cognitive development, and five of 18 for social and emotional wellbeing. However, most positive effects were in studies at high or unclear risk of bias, within-study effects were inconsistent, and negative effects were also seen. Intervention content and intensity varied greatly, but this was not associated with effectiveness. The quality of evidence overall was low as judged by GRADE criteria. Interpretation: Evidence that interventions to enhance universal health services up to 2 years postpartum are effective for improving child development is weak. There is an urgent need for more robust assessment of existing interventions, and to develop and evaluate novel interventions to enhance the universal offer. Funding: Public Health Wales.